Exploring the perceptions of literacy in assessment for learning among high school English teachers - Sukarno Sukarno; Nur Hidayanto Pancoro Setyo Putro; Ihtiara Fitrianingsih; Yasir Ayed Alsamiri; Fadhl Mohammed Awadh Gharamah; Ingrid A. Gavilan Tatin (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2024)
In the field of English language education, the crucial role of assessment for learning (AfL) requires teachers to possess robust assessment literacy. This study explores AfL literacy among high school English teachers in Yogyakarta, Indonesia by utilizing Alonzo's validated AfL survey that establishes a comprehensive six-factor model, delineating teachers as assessors, pedagogists, student partners, motivators, learners, and stakeholder partners. Exploiting confirmatory factor analysis and examining demographic variations, this quantitative research invited 202 English teachers in the Special Region of Yogyakarta, Indonesia selected purposively based on the geographical service area. Data were collected through an online questionnaire adopting Alonzo's 42-questions AfL and were analyzed quantitatively via Confirmatory Factor Analysis (CFA) with four indices, namely comparative fit index (CFI), Tucker-Lewis index (TLI), root mean square error of approximation (RMSEA), and standard root mean square residual (SRMR).The findings substantiate the efficacy of the six-factor AfL model, underscoring educators' roles extending beyond traditional frameworks. The investigation also introduces a tool featuring detailed performance descriptors, addressing deficiencies, and harmonizing with AfL principles. It deduces that heightened foundational comprehension among English educators cultivates enhancements in AfL literacy and propels the refinement of professional evaluative competencies, thereby enriching the nuanced discourse surrounding AfL within language pedagogy. While the study's scope is confined to a specific geographical area and a limited cohort of participating instructors, it significantly enriches our comprehension of AfL literacy among English pedagogies. This research, therefore, provides a foundation for professional growth initiatives and facilitates enhancements in pedagogical approaches and academic achievement.